Bridging Communities and Healthcare: Empowerment Strategies for Effective JKN Program Governance - Karimah, Akhlaqul; DZ, Fariza Anaqoh; Hidayah, Iftita Nurul; Ahmadinda, Maura; Ramadhani, Nanda Ayu; Mika Vernicia Humairo (Inovasi Lokal, 2025)
This research evaluates community empowerment strategies in managing the National Health Insurance Program (JKN) through role-playing simulations and participatory approaches. The collaborative method involved 10 groups of students who were given patient referral scenarios (preeclampsia, child fever, stroke) to enhance their understanding of healthcare service dynamics. Simulation results show that this method effectively enhances multidisciplinary collaboration skills, such as communication between healthcare facilities and emergency decision-making. However, challenges such as the limited number of ambulances and the low public understanding of referral procedures still hinder the implementation of JKN. Post-simulation reflections recommend continuous training for health cadres and optimizing communication technology to accelerate coordination. This study emphasizes the importance of integrating community empowerment into the JKN strategy to strengthen active community participation and achieve inclusive universal health coverage.